2016
DOI: 10.1088/0957-4484/27/42/425301
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic extended misfit dislocations in overcritical SiGe films by local substrate patterning

Abstract: In this work we will show how local substrate patterning leads to a long range controlled propagation of dislocations in SiGe films grown on Si(001) substrates. Dislocations preferentially nucleate in the inhomogeneous strain field associated with the patterned pits, and then partialize on the local (111) surfaces which form the pit sidewalls. The resulting V-shaped defects extend for several microns and effectively block the propagation of randomly nucleated dislocations which propagate in the perpendicular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This concept works quite well; for example, Gatti et al [51] demonstrated this by employing {111} facets in the form of trenches along the [110] directions on (001) substrates as preferential nucleation centers for dislocation loops. Similar concepts are demonstrated by Grydlik et al [52] or Bollani et al [53], where {111} faceted pit structures are employed. Here, TEM investigations prove that the compressive strained SiGe layer on the {111} facets leads to stacking faults.…”
Section: Dislocations In Sige Heterostructuressupporting
confidence: 56%
“…This concept works quite well; for example, Gatti et al [51] demonstrated this by employing {111} facets in the form of trenches along the [110] directions on (001) substrates as preferential nucleation centers for dislocation loops. Similar concepts are demonstrated by Grydlik et al [52] or Bollani et al [53], where {111} faceted pit structures are employed. Here, TEM investigations prove that the compressive strained SiGe layer on the {111} facets leads to stacking faults.…”
Section: Dislocations In Sige Heterostructuressupporting
confidence: 56%